PRODUCTION OF ACTIVATED CARBON FROM SUBBITUMINOUS COAL USING ROTARY KILN AND CYCLONE BURNER - IKA MONIKA; SLAMET SUPRAPTO (Puslitbang tekMIRA, 2011)
Research on the production of activated carbon from coal has been carried out by Research and Develop- ment Center for Mineral and Coal Technology since 1980 in the laboratory as well as pilot plant scale. Production of activated carbon from coal using rotary kiln and oil burner at the pilot plant of 1 ton/day has been carried out successfully to produce good quality product. To reduce the dependence upon using oil fuel, the oil fuel burner was replaced by coal fueled cyclone burner. Product quality and economic evalua- tion of the production of activated carbon using the burners are described in this paper. The coal used was subbituminous coal from Air Laya, South Sumatera. The coal passing 3 cm screen was carbonized at 500- 600° C for 2 hours to produce good quality char. The variables of activation process observed were con- sisted of particle size of char (+6, -6+12 and -12 +20 mesh) and residence time (1.5, 3 and 6 hours). The results showed that the optimum condition for activation process was using particle size of -6+12 mesh and residence time at a minimum of 3 hours. The activated carbon produced showed quality which fairly met the requirement of Indonesian Industrial Standard with iodine number of 600-800 mg/g compared with stan- dard of 750-1200 mg/g and market quality of 400-1200 mg/g. Eventhough the adsorption capacity obtained was at the lowest limit of the Indonesian Industrial Standard, however the pre utilization test showed that the product could be used for treatment of shrimp farms water.